FRI0158 Microscopic hematuria in temporal arteritis. (1st June 2001) - Vanderschueren, SM; Depoot, I; Knockaert, DC; Bobbaers, H
Abstract : Background: Temporal arteritis (TA) is traditionally considered to spare the kidney, although an uncontrolled study reported microscopic hematuria in 10 out of 30 patients with TA. 1 Objectives: To study the incidence and characteristics of microscopic hematuria in TA. Methods: We studied retrospectively 41 patients with biopsy-proved TA (the TA-patients), 41 patients with polymyalgia rheumatica (the PMR-patients) and 43 patients over 65 years of age admitted to the general internal medicine unit (the control patients). Urinalysis and urine microscopy were performed. Microscopic hematuria was defined as the presence of more than 5 red blood cells (RBCs) per high-power field. Patients with pyuria, significant bacteriuria or known urologic or nephrologic disorders were excluded. Results: Heem (trace or more) in the urine was present in 41.0% patients of the AT-patients, versus in 22.2% of the PMR-patients (p = 0.14) and in 21.4% of the control patients (p = 0.095). Microscopic hematuria was significantly more frequent in the AT-patients (Table 1 ). Presenting symptoms, renal function, arterial blood pressures, degree of proteinuria and of leucocyturia did not differ between AT-patients with and without microscopic hematuria. Urinary RBCs were predominantly dysmorphic in all 7 AT-patients in whom RBC-morphology was assessed. In 2 patients RBC-casts were present. Biopsy in one of them confirmed renal vasculitis. In 69.2% of the AT-patients microscopic hematuria disappeared after initiation of corticosteroid therapy. Conclusion: Microscopic hematuria of renal origin in TA is frequent but generally benign. Its presence, if unassociated with blood pressure elevation or renal function deterioration, serves to rule in rather than rule out the diagnosis of TA. In the typical setting invasive urologic and nephrologic work-up is not warranted. Reference: Manna R, Cristiano G, Todaro L, Latteri M, Gasbarinni G. Microscopic hematuria: a diagnostic aid in giant-cell arteritis? Lancet 1997;350:1226